ANALISIS STRATEGI PEMASARAN PADA USAHA KECIL MENENGAH PERCETAKAN (STUDI KASUS UKM PERCETAKAN THE BEJOS SCREEN PRINTING, KOTA PALOPO, SULAWESI SELATAN) - Syafaruddin, Syafaruddin; Amin, Amelia Rezky; Adil, Muhammad (COMPETITIVENESS, 2019)
The Bejos Screen Printing is one of the SMEs located in palopo city, South Sulawesi that has been growing since 2013, The Bejos Screen Printing printing produces screen printing clothes Since starting its business The Bejos Screen Printing senatisa faced with various obstacles and obstacles, the number of similar companies that appear to make Printing The Bejos Screen Printing difficult to maintain the position of its products due to increasingly tight industry competition. Strict competition conditions are a problem faced by The Bejos Screen Printing. The purpose of this research is to determine the marketing strategy of SME printing through SWOT analysis. In determining marketing strategies it is necessary to know the internal factors of strengths and weaknesses, external factors of opportunities and threats. The strategy that can be applied is the ST Strategy is a strategy that uses the power that the company has to overcome threats or commonly referred to as diversification strategies. Keywords: UKM The Bejos Screen Printing, SWOT Analysis, marketing strategy